Determining suicide risk in trauma patients using a universal screening program. Issue 1 (July 2018) - Imran, Jonathan B.; Richmond, Robyn E.; Madni, Tarik D.; Roaten, Kimberly; Clark, Audra T.; Huang, Emily Y.; Mokdad, Ali A.; Taveras, Luis R.; Abdelfattah, Kareem R.; Cripps, Michael W.; Eastman, Alexander L.
Abstract : BACKGROUND: Trauma patients may be at elevated risk for subsequent suicide; however, it is unclear whether patients at risk can be identified during their initial presentation following injury. The objectives of this study were to evaluate the use of a standardized clinical decision support system for suicide risk screening developed by our hospital system and to determine the incidence of positive suicide screenings in our trauma population. METHODS: Adult trauma patient screenings were performed by nursing staff during the triage process using the Columbia Suicide Severity Rating Scale, Clinical Practice Screener, Recent (C-SSRS). Adult trauma patients who had a suicide risk screening completed from February 2015 to November 2015 were evaluated retrospectively. Patients were divided into cohorts consisting of those with positive and negative screening assessments. Significance was set at α = 0.05. Statistical analysis was performed using Student t test and a χ 2 test where appropriate. RESULTS: Overall, 3, 623 of 3, 712 patients (98%) completed a suicide risk screening during the study period. Those who went unscreened were not evaluated due to altered mental status/intubation/emergent surgery (97%), death (1%), or an unwillingness to cooperate (2%). The suicide risk screening result was positive in 161 of 3, 623 patients (4%) in the study cohort. On univariate analysis, patients with a positive suicide risk screen result were more likely to be white (43% vs 32%; p = 0.01), identify English as their primary language (91% vs 73%; p < 0.01), have insurance coverage (48% vs 28%; p < 0.01), and were more likely to initiate a low-level trauma activation (27% vs 16%; p <0.01) than those who had a negative screening result. A positive suicide risk assessment result was moderately associated with patients of white race (odds ratio, 1.83; 95% confidence interval, 1.27–2.65) on multivariable logistic regression. CONCLUSION: Our universal suicide screening process identifies an at-risk subpopulation of trauma patients. LEVEL OF EVIDENCE: Prognostic study, level III; therapeutic, level IV.